The role of cultural and social factors in the formation of Persian grammar - Alfili, Evan (Al-Adab Journal, 2023)
A feature of the language is its movement, step-by-step development and transformation with social developments. The faster the social changes, the more changes the language will experience. the more language transformation is not only due to the influence of other languages; language itself is also inherently dynamic transformed and developed due to changing social needs. Language development is usually slow and gradual, but the sudden influx of foreign languages due to increased political power and cultural influence on one hand and radical change in social needs on the other, may accelerate the development of language in a certain period of history. On the other hand, the basis of the language is based on syntax. Two languages can be considered different when their structure differs even if their vocabulary remains the same. Therefore, if there are changes in the syntax of a language, then the basis of that language will change. This is the status of the Persian language in the present era. Scholars divided the Persian language into three periods throughout history. In all three periods of the history of the Persian language, there have been developments and changes in the language, both in terms of vocabulary, sounds and grammar. But the speed of changes in the third or current period is much higher than in previous periods. One of the important factors for the rapid linguistic developments in the current era is the intense communication with others and the influx of works translated into Persian from foreign languages. The rise of the Internet and social networks and as a result the doubling of content production on this platform has become an additional reason and we are witnessing a new era in linguistic developments. The shift in natural vocabulary and the borrowing of other words often enriches the language, but this issue in the grammatical part is serious and will cause confusion for speakers of the borrowed language; a problem that has already sounded the alarm for several reasons in the current language period.